LEADERSHIP «SOFT SKILLS»: THE KEY TO SUCCESSFUL EDUCATIONAL MANAGEMENT - Pyshchyk , Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
This article examines ways to enhance the communicative culture of educational leaders with an emphasis on the importance of «soft skills». Strategies for developing flexible skills, which are crucial for leadership and management in the modern educational sector, are discussed. The main aspects of how communicative competence affects the professional effectiveness of leaders, including the ability to establish business contacts and adapt to changing management conditions, are revealed. Research results confirm that the development of «soft skills» is key in enhancing the competitiveness of educational leaders. Conclusions are made about the necessity to integrate effective training methodologies for flexible skills into professional development processes.